PENGARUH KOMITMEN ORGANISASI, SIKAP KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA DIVISI SDM PT PLN (PERSERO) PUSLITBANG KETENAGALISTRIKAN - Denny Yoristar; Dicky Fardian (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2021)
The research objective is to determine the influence of Organizational Commitment, Work Attitude and Job Satisfaction on Employee Performance of PT PLN (Persero) Electricity Research and Development Center in the HR Division. Secondary and primary data sources. Primary data obtained questionnaires to 34 employees as respondents. Multiple regression analysis method using IBM SPSS 22. From the results of the study showed that organizational commitment has a significant influence on employee performance, work attitudes have a significant influence on employee performance, job satisfaction has a significant influence on employee performance, and simultaneously organizational commitment, work attitude and Job Satisfaction has a significant influence on Employee Performance.